2023
DOI: 10.5194/amt-16-5051-2023
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of detection and quantification methods for methane emissions from the natural gas distribution network in Hamburg, Germany

Hossein Maazallahi,
Antonio Delre,
Charlotte Scheutz
et al.

Abstract: Abstract. In August and September 2020, three different measurement methods for quantifying methane (CH4) emissions from leaks in urban gas distribution networks were applied and compared in Hamburg, Germany: the “mobile”, “tracer release”, and “suction” methods. The mobile and tracer release methods determine emission rates to the atmosphere from measurements of CH4 mole fractions in the ambient air, and the tracer release method also includes measurement of a gaseous tracer. The suction method determines emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…A disadvantage of this approach is that many streets were surveyed only once or twice. Controlled release experiments , and frequent passages of the same leak location have shown that emission estimates from a single detected source can vary by more than an order of magnitude between individual passages and that emission rate estimates based on infrequent visits are biased high. A simple explanation for changing local enhancements is changes in wind speed and direction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A disadvantage of this approach is that many streets were surveyed only once or twice. Controlled release experiments , and frequent passages of the same leak location have shown that emission estimates from a single detected source can vary by more than an order of magnitude between individual passages and that emission rate estimates based on infrequent visits are biased high. A simple explanation for changing local enhancements is changes in wind speed and direction.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative methodology is published by Marcogaz 14 and uses gas distribution network length, network (pipeline) material, pipeline material-specific emission factors, and the number of connection points and city gates to estimate methane emissions. Methane emission from total national gas distribution networks have been calculated using the emission factors and gas distribution network data presented in Marcogaz 14 and subsequently downscaled to each city based on population data, 19 similar to the procedure for the NIR CRF emission estimates. The table with city-specific values can be found in Section S5 .…”
Section: Methodsmentioning
confidence: 99%
“…Various techniques can be used to estimate methane emissions. For instance, methane concentrations can be measured locally in ambient air with gas analyzers (e.g., Maazallahi et al 2023; MacMullin and Rongère 2023; Kumar et al 2021) or regionally in the atmosphere using satellite, drone, and other imagedbased techniques (Pandey et al 2023;Duren et al 2019). Another strategy can be followed in the very speci c case of natural gas network utilities.…”
Section: Quanti Cation Of Unaccounted For Gasmentioning
confidence: 99%